Organs-on-a-chip for global equity: a perspective from Guatemala on advancing biomedical research in resource-limited settings - Cabrera, Maria D.; del Valle, Andrea C. (Frontiers in Lab on a Chip Technologies, 2025)
Animal models have long supported biomedical research, particularly in the development of drugs and preclinical testing. Yet, persistent discrepancies between animal data and human clinical outcomes have prompted a critical reassessment of their translational value. Challenges, including biological variability, inadequate methodological reporting, and limited regulatory oversight, particularly in low- and middle-income countries, undermine the reliability of animal research in guiding clinical practice. Organ-on-a-chip (OoC) technology offers a compelling alternative, especially relevant for resource-limited contexts. These microengineered systems enable more accurate modeling of human physiology and better predictions of drug safety and effectiveness, yielding direct benefits for underserved populations. By incorporating patient-derived cells, OoC platforms allow the study of region-specific diseases while fostering international research collaboration. Moreover, such approaches reduce reliance on costly animal research infrastructure, addressing critical barriers in countries like Guatemala, where the legal framework and funding remain limited. We argue that broader adoption of OoC technology is essential to improving research equity, quality, and accessibility worldwide. This perspective reflects the realities and aspirations of the Guatemalan scientific community, where advancing alternatives to animal models is not only a scientific priority but also a pathway to greater participation in global biomedical research.